The relationship between a child's affect regulation and their social cognition (theory of mind and empathy) - Diara, Heesoo Melanie (Department of Psychology, 2026)
Affect regulation is an essential component of human development and is crucial for successful social functioning and emotional health. Similarly social cognitive skills like empathy and Theory of Mind (ToM) are also necessary for successful social understanding and interaction in childhood. Researchers have reported associations between affect regulation and social cognition. For example, research shows that affect regulation is essential for empathic concern and behaviour. Additionally, studies in clinical populations have highlighted the relationship between affect regulation and ToM. Based on the literature, it was inferred that successful regulation of one's affect would result in greater empathic and ToM ability. Hence the study hypothesized that children's affect regulation would positively predict their empathy and ToM, over and above any effects of the covariates (age, IQ and working memory, gender, household income or highest level of maternal education (HLOE)). Data collected from one hundred and eighty five (N = 185) neuro-typical primary school children between the ages of 6 and 13, from three mainstream public primary schools in Cape Town was analysed. The results found no significant association between participant affect regulation scores and their empathy and ToM scores. Thus, it was concluded that affect regulation was not a significant predictor of social cognition in this sample.